2016
DOI: 10.3928/01484834-20160316-03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Summer Bridge: Critical Component of the Leadership 2.0 Program

Abstract: The summer bridge was effective in preparing nursing students for the first year of college. Through holistic evaluation, unique aspects of socialization critical to student success were uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The need for nursing care has increased in recent years in Poland, as well as in other European countries and worldwide, due to the aging of society and the increasing incidence of chronic diseases [1][2][3][4][5][6][7][8][9]. At the same time, the number of nurses is decreasing rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The need for nursing care has increased in recent years in Poland, as well as in other European countries and worldwide, due to the aging of society and the increasing incidence of chronic diseases [1][2][3][4][5][6][7][8][9]. At the same time, the number of nurses is decreasing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Both national and international literature on the issue of leadership in nursing emphasize the difference between the role of leaders and the role of managers of health care institutions, including nursing managers and ward nurses [2][3][4][5][6][7][8]. The role of leaders is to effectively design the change and drive its implementation, while health care managers are more responsible for the productivity of work in the organization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study exploring the impact of a bridge program for students in STEM majors found that students attributed faculty mentors in the bridge program as being particularly important to their academic success (Maton, Hrabowski, & Schmitt, 2000). Similarly, another study exploring the impact of a bridge program for nursing students showed that students ranked the social aspects of the bridge program as the most important part of the experience (Pritchard et al, 2016). However, no study has explored student comfort levels and the number of connections students make with peers and faculty.…”
mentioning
confidence: 99%